2019
DOI: 10.1002/acp.3595
|View full text |Cite
|
Sign up to set email alerts
|

Why should we try to think like scientists? Scientific reasoning and susceptibility to epistemically suspect beliefs and cognitive biases

Abstract: SummaryThis paper examines whether scientific reasoning skills predict people's susceptibility to epistemically suspect beliefs and cognitive biases. We used the recently developed Scientific Reasoning Scale (SRS) because it measures the ability to read and evaluate scientific evidence. Alongside the SRS, 317 participants aged 18–30 years completed measures of thinking dispositions and cognitive ability to ascertain whether the SRS contributes specifically to susceptibility to epistemically suspect beliefs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 51 publications
8
55
0
2
Order By: Relevance
“…Unwarranted or epistemically suspect beliefs including conspiracy beliefs have previously been referred to as 'contaminated mindware' 54 . These beliefs have repeatedly been shown to be strongly interrelated [55][56][57] , and to share common predictors, such as ontological confusions 56,58 , the inhibition of analytical reasoning 59 , preference of intuitive over analytic thought 60 , lower levels of scientific reasoning 55,61 and anti-science attitudes 58 . In this section, these beliefs, reasoning processes, and attitudes will be reviewed with regards to belief in COVID-19 conspiracy theories.…”
Section: Beliefs Biases and Attitudesmentioning
confidence: 99%
“…Unwarranted or epistemically suspect beliefs including conspiracy beliefs have previously been referred to as 'contaminated mindware' 54 . These beliefs have repeatedly been shown to be strongly interrelated [55][56][57] , and to share common predictors, such as ontological confusions 56,58 , the inhibition of analytical reasoning 59 , preference of intuitive over analytic thought 60 , lower levels of scientific reasoning 55,61 and anti-science attitudes 58 . In this section, these beliefs, reasoning processes, and attitudes will be reviewed with regards to belief in COVID-19 conspiracy theories.…”
Section: Beliefs Biases and Attitudesmentioning
confidence: 99%
“…First, we focus on the key question of whether anxiety and lack of control are related to the increased endorsement of coronavirus-specific conspiracy theories and epistemically suspect beliefs in general. As the endorsement of all three types of epistemically suspect beliefs is strongly intercorrelated (see also Čavojová et al, 2020;Lobato et al, 2014;Šrol, n.d.), we have calculated a single composite score by averaging the ratings on all 19 items of the epistemically suspect belief questionnaire (M = 2.52, SD = 0.68, α = .89). Both anxiety and lack of control are consistently positively related to the endorsement of coronavirus-specific conspiracies as well as generic epistemically suspect beliefs.…”
Section: Correlates Of the Coronavirus-specific And Generic Epistemicmentioning
confidence: 99%
“…An open question is whether threatening events prompt people to adopt conspiracy beliefs pertaining to that specific situation or rather they stimulate a mentality in which people endorse more epistemically suspect beliefs 1 in general. Previous research showed that people who believe in some specific conspiracy theories are very prone to hold other non-related conspiracy beliefs as well (Swami, Chamorro-Premuzic, & Furnham, 2010), and they are also much more likely to accept paranormal and pseudoscientific claims (e.g., Čavojová et al, 2020;Lobato et al, 2014;Šrol, n.d.). A study by Lewandowsky, Oberauer, and Gignac (2013;however, see Landrum & Olshansky, 2019) further shows that conspiratorial ideation may be the key factor in explaining the rejection of well-established scientific findings and subsequently, the endorsement of pseudoscientific beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that most previous research on the topic did not control for familiarity with the presented pseudoscientific statements (Čavojová, Šrol, & Jurkovič, 2019;Fasce & Picó, 2019a;Lobato et al, 2014;Majima, 2015;Mercier, Majima, & Miton, 2018;Swami et al, 2012Swami et al, , 2016van Elk, 2019). In some studies, the construction of the scales implied knowledge about all or some pseudoscientific claims by including items starting with "I believe" (Lewandowsky et al, 2013;Rutjens et al, 2018) or by directly asking participants to use their general knowledge about a particular field (Bensley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%